The lysosome as a novel therapeutic target of EGFR-mediated tumor inflammation - Sung, Woo Jung; Kim, Dohyang; Zhu, Anlin; Cho, Namki; Yoo, Hee Min; Noh, Ji Heon; Kim, Kyoung Mi; Lee, Hyun-Su; Hong, Jaewoo (Frontiers in Pharmacology, 2022)
EGFR-mediated tumors have been targeted to overcome several different malignant cancers. In order that EGFR overexpression and mutations are directly related to the malignancy, and this makes the therapy more complicated. One of the reasons of the malignancy is the induction of AP1 followed by inflammation via IL-6 secretion. Current therapeutic strategies to overcome EGFR-mediated tumors are tyrosine kinase inhibitors (TKIs), anti-EGFR monoclonal antibodies and the combination of these two agents with classic chemotherapy or immune checkpoint inhibitors (ICIs). Although the strategies are straightforward and showed promising efficacy in several studies, there are still hurdles to overcome the adverse effects and limited efficacy. In this study we review the current therapeutic strategies to target EGFR family members and how they work as well as the effect and limitations. We also suggest developing novel strategies to target EGFR-mediated tumors in a novel approach. Lysosome is the main custodial staff to discard unwanted amount of EGFR and other receptor tyrosine kinase molecules, targeting this organelle maybe a new approach to overcome EGFR-mediated cancers.